Protozoal abortion in farm ruminants: guidelines for diagnosis and control - Ortega-Mora, L. M.; Buxton, D.; Buxton, D.; Conraths, F. J.; Conraths, F. J.; Gottstein, B.; Gottstein, B.; Ortega-Mora, L. M. (Wallingford :CABI, 2007)
This book contains guidelines for the diagnosis and control of protozoal reproduction losses in farm ruminants. This book is comprised of 5 chapters covering the following: reproductive problems in cattle and sheep; sample collection; aetiological diagnosis; differential diagnosis of protozoal abortion in farm ruminants; and control measures.
Keywords: LL250 - Animal Reproduction and Embryology, (New March 2000); LL822 - Protozoan, Helminth, Mollusc and Arthropod Parasites of Animals, (New March 2000); LL860 - Non-communicable Diseases and Injuries of Animals; LL886 - Diagnosis of Animal Diseases, (New March 2000)